МУЛЬТИПЛЕКС ПЦР ДЛЯ ОДНОВРЕМЕННОЙ ДИФФЕРЕНЦИАЛЬНОЙ ДИАГНОСТИКИ ГРИППА А И БОЛЕЗНИ НЬЮКАСЛА (Experimental biology, 2015)
Developed based on the original Kazakh strains of PCR test-system can be used in practice for Veterinary Virology and epizootiology for differential diagnosis of outbreaks of influenza A and Newcastle disease in populationsof wild and domestic birds.
Keywords: domestic birds; test-system